2014
DOI: 10.1108/imcs-01-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Perceived significance of information security governance to predict the information security service quality in software service industry

Abstract: Purpose – Information security is a growing concern in society, across businesses and government. As the offshore IT services market continues to grow providing numerous benefits, there are also perceived risks with respect to the quality of information security delivered in the supply chain. This paper aims to examine, as a case, the perceptions of Indian software services provider (service provider) employees with respect to information security governance and its impact on information securi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Corresponding to the Leavitt's model (1965), the fifth hypothesis posits a relationship between an organisation's (or potentially the healthcare system's) ability to respond to cross-scale dynamics, coded as Interdependence, and its Security in Transformation. This is in line with empirical studies which have suggested that knowledge generated by establishing interdependence and value-based convergence between organisations and their supply chain can be an effective tool to tackle cyber security issues (Bahl and Wali, 2014;Neal and Ilsever, 2016). Hypothesis 6.…”
Section: Hypotheses Developmentsupporting
confidence: 82%
“…Corresponding to the Leavitt's model (1965), the fifth hypothesis posits a relationship between an organisation's (or potentially the healthcare system's) ability to respond to cross-scale dynamics, coded as Interdependence, and its Security in Transformation. This is in line with empirical studies which have suggested that knowledge generated by establishing interdependence and value-based convergence between organisations and their supply chain can be an effective tool to tackle cyber security issues (Bahl and Wali, 2014;Neal and Ilsever, 2016). Hypothesis 6.…”
Section: Hypotheses Developmentsupporting
confidence: 82%
“…Customers are more likely to trust a new service if adequate security is provided for their transaction data (Singh and Srivastava, 2020). Bahl & Wali (2014) explained that customer information security reflects the company service quality offered to customers. Logically, most customers prefer a high-quality product, such as the security dimension, which will increase their satisfaction in using that secure product.…”
Section: Security Dimensionmentioning
confidence: 99%
“…Reference [9] showed that information security governance as one of the parts of corporate governance urges information security service. This can help organizations to deal with information security risks through providing stable service quality meeting the expectations of their customers, learning about customer expectations and reducing the gap between customer perception and expectations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Security incidents are happening almost every day, and they are caused by hackers, spam, viruses, spyware, zombie networks and many other threats. These incidents can have significant impact on the economy and society by violating human rights and a lot of organizations have suffered failures, serious losses and extinction due to lack of security, privacy and governance of this asset [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation